2012
DOI: 10.1603/me12061
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of <I>Aedes japonicus japonicus</I> and Its Colonization of Container Habitats in Michigan

Abstract: Oviposition dynamics and colonization of container habitats by the invasive species, Aedes (Finlaya) japonicus japonicus (Theobald) were examined through the use of ovistrips placed in buckets, and larval surveys of tree holes and tires at sites in central Michigan. In general, oviposition and colonization increased during the study periods, with several sites showing large increases from <10% Ae. j. japonicus initially to over 60% in the following years. Seasonally, higher proportions of Ae. j. japonicus were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…j. japonicus is active for a longer spring through fall period compared with similar container-dwelling mosquitoes (see above). This is also true in its expanded range (e.g., 4, 15, 27, 50). In some larval habitats, Ae.…”
Section: Phenology and Temperature Tolerancesmentioning
confidence: 76%
See 4 more Smart Citations
“…j. japonicus is active for a longer spring through fall period compared with similar container-dwelling mosquitoes (see above). This is also true in its expanded range (e.g., 4, 15, 27, 50). In some larval habitats, Ae.…”
Section: Phenology and Temperature Tolerancesmentioning
confidence: 76%
“…j. japonicus is a cold-tolerant species that overwinters primarily in the egg stage (for egg surface characteristics, see 34), but sometimes in the larval stage (4, 5, 41, 50, 93). Bartlett-Healy et al (10) observed that Ae.…”
Section: Phenology and Temperature Tolerancesmentioning
confidence: 99%
See 3 more Smart Citations